The kinetic study of clarification of Thai waters by the SIROFLOC process - Yu, Dongmei; I, Fude; Shin, H. S.; Hanaki, K.; Dixon, D. R.; Fish, E. J.; Wang, R. R.; KEIDANREN, Japan (Bangkok : Asian Institute of Technology, 1987)
The SIROFLOC Process for removing turbidity and color colloids from a raw water by their adsorption onto very fine magnetite particles was developed by CSIRO of Australia. The applicability of SIROFLOC Process to waters Chao Phrya River of Thailand in removing turbidity and co lor had been considered on a laboratory scale in an ea lier study. The kinetic properties of the process we re studied in this research. A simple mathematical model of the adsorption process, which agrees well with the experimental data has been worked out, which can be used to optimize the process design. Several samples were jar-tested using a modified experimental procedure to investigate the kinetics of turbidity removal of Chao Phaya River water . The optimum conditions such as pH level, dosage of magnetite and dosage of polyelectrolyte were found for the kinetic study. The most interesting feature of the results is the very rapid initial rate of adsorption followed by a s low tailing off over a period of several minutes. The kinetic model, which include s three constants, agreed well with the curve of ad sorption process suggested by the kinetic data. One constant, K2 can be given a fixed value of 0.4 min-1, which l eaves only two constants which is to be fitted with all the adsorption data. The results of this analysis lent considerable support to the validity of t he proposed model as, not only an excellent fit was obtained to t he experimental data, but also the variation of Kl and Cm under experimental conditions correlate closely with the adsorption mechanism.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Sewage -- Purification -- Flocculation